Romantic medievalism from a new comparative perspective - Seweryn, Dariusz (Colloquia Litteraria, 2017)
From certain point of view a desperate defense of an aesthetic doctrine of classicism, undertaken by Jan Śniadecki, a Polish mathematician and astronomer of the eighteenth century, resembles the E. R. Curtius’ thesis on “Latinism” as a universal factor integrating European culture; it may be stated that post-Stanislavian classical writers in Poland were driven by the same “concern for the preservation of Western culture” which motivated Ernst Robert Curtius in the times of the Third Reich and after its collapse. But the noble-minded intentions were in both cases grounded on similarly distorted perspective, which ensued from a mistificatory attitude towards a non-Latin heritage of the European culture. The range of that mystification or delusion has been fully revealed by findings made by modern so-called new comparative mythology/philology. Another aspect of the problem is an uniform model of the Middle Ages, partially correlated with the Enlightenment-based stereotype of “the dark Middle Ages”, which despite of its anachronism existed in literary studies for a surprisingly long period of time. Although the Romantic Movement of 18th – 19th centuries has been quite correctly acknowledged as an anti-Latinistic upheaval, its real connections with certain traditions of Middle Ages still remain not properly understood. Some concepts concerning Macpherson’s The Works of ossian, put forward by modern ethnology, may yield clues to the research on the question. As suggested by Joseph Falaky Nagy, Macpherson’s literary undertaking may by looked into as a parallel to Acallam na Senórach compiled in Ireland between 11th and 13th centuries: in both cases to respond to threats to the Gaelic culture there arose a literary monument and compendium of the commendable past with the core based on the Fenian heroic tradition that was the common legacy for the Irish and Highlanders. Taking into consideration some other evidence, it can be ascertained that Celtic and Germanic revival initiated in the second half of 18th century was not only one of the most important impulses for the Romantic Movement, but it was also, in a sense, an actual continuation of the efforts of mediaeval writers and compilers (Geoffrey of Monmouth, Snorri Sturluson, Saxo Grammaticus, anonymous compilers of Lebor gabála Érenn and Acallam, Wincenty Kadłubek), who would successfully combine Latin, i.e. classical, and ecclesiastical erudition with a desire to preserve and adapt in a creative way their own “pagan” and “barbarian” legacy. A special case of this (pre)Romantic revival concerns Slavic cultures, in particular the Polish one. Lack of source data on the oldest historical and cultural tradition of Slavic languages, especially in the Western region, and no record about Slavic tradition in highbrow literary culture induced two solutions: the first one was a production of philological forgeries (like Rukopis královédvorský and Rukopis zelenohorský), the second one was an attempt to someway reconstruct that lost heritage. Works of three Romantic historians, W. Surowiecki, W. A. Maciejowski, F. H. Lewestam, shows the method. Seemingly contradicting theories they put forward share common ground in aspects which are related to the characteristics of the first Slavic societies: a sense of being native inhabitants, pacifism, rich natural resources based on highly-effective agriculture, dynamic demography, a flattened social hierarchy and physical prowess. The fact of even greater importance is that the image of that kind has the mythological core, the circumstance which remains hitherto unnoticed. Polish historians not only tended to identify historical ancient Slavs with mythical Scandinavian Vanir (regarding it obvious), but also managed to recall the great Indo-European theme of ”founding conflict” (in Dumézilian terms), despite whole that mythological model being far beyond the horizon of knowledge at that time. Despite all anachronisms, lack of knowledge and instrumental involvement in aesthetic, political or religious ideology, Romanticism really started the restitution of the cultural legacy of the Middle Ages, also in domain of linguistic and philological research. The consequences of that fact should be taken into account in literary history studies.